The Role of Digital Technologies in Enhancing Effectiveness of Museum Services - Kurbanov Firuz Golibovich (Garuda Prestasi Nusantara Consulting, 2021)
The article discusses issues related to the communication system of museum services and perspective aspects of the development of communication in this area based on the widespread use of digital technologies. The development of museum services, as a special sphere of spiritual education and the application of labor, is of great importance in the life of society. The place of the museum in the socio-cultural space of society is determined by the natural desire of a person to study his spiritual and material world, as well as the desire to familiarize himself with universal human spiritual and cultural values. In this regard, the role of the museum is significant, as the custodian of the cultural and historical values ​​of society. Keywords: museum, museum services, economic stability, museum audience, communication, digital technologies